Human Ambition and Identity Crisis in Ibn ‘Athaillah al-Sakandari’s Sufism - Abdulloh Hanif; Miftakhur Rohman Rohman (Journal of Sufism and Psychotherapy, 2026)
Human life is inseparable from economic and status issues. Both often force people to do anything just to achieve them. However, without a strong ambition to achieve these goals, humans will not continue to move forward and will only remain where they are now. On the other hand, religion often talks about humans being grateful and accepting their circumstances, where these expressions often become capital for laziness and an excuse to not want to try in life. This study aims to explain that religion does not tell humans to be silent and wait for miracles, but the concept of Qona'ah, Tawakkal and others are principles that humans need to understand which must always accompany human endeavors to avoid falling into worldly luxury. This research was conducted using qualitative research methods through literature studies involving critical analysis of related phenomena, especially in Indonesia. By using qualitative research methods, this study aims to find a new meaning of the concept of Qona'ah from the perspective of Ibn Athallah to provide a breath of fresh air to society about the meaning of ambition that is appropriate to its level. Ultimately, this research found that Ibn Athalillah wisely explained that humans may have ambitions to achieve something, but this should not be the primary goal, as it would hinder gratitude and acceptance of God's will. Accepting fate does not mean abandoning effort altogether. Rather, it is a way to be grateful even if the outcome is not as desired.